EndoC-βH1 cells display increased sensitivity to sodium palmitate when cultured in DMEM/F12 medium. Issue 3 (4th May 2017) - Krizhanovskii, Camilla; Kristinsson, Hjalti; Elksnis, Andris; Wang, Xuan; Gavali, Hamid; Bergsten, Peter; Scharfmann, Raphael; Welsh, Nils
ABSTRACT: Aims - Human pancreatic islets are known to die in response to the free fatty acid of sodium palmitate when cultured in vitro . This is in contrast to EndoC-βH1 cells, which in our hands are not sensitive to the cell death-inducing effects sodium palmitate, making these cells seemingly unsuitable for lipotoxicity studies. However, the EndoC-βH1 cells are routinely cultured in a nutrient mixture based on Dulbecco's Modified Eagle Medium (DMEM), which may not be the optimal choice for studies dealing with lipotoxicity. The aim of the present investigation was to define culture conditions that render EndoC-βH1 cells sensitive to toxic effects of sodium palmitate. Methods - EndoC-βH1 cells were cultured at standard conditions in either DMEM or DMEM/F12 culture medium. Cell death was analyzed using propidium iodide staining and flow cytometry. Insulin release and content was quantified using a human insulin ELISA. Results - We presently observe that substitution of DMEM for a DMEM/Ham's F12 mixture (50%/50% vol/vol) renders the cells sensitive to the apoptotic effects of sodium palmitate and sodium palmitate + high glucose leading to an increased cell death. Supplementation of the DMEM culture medium with linoleic acid partially mimicked the effect of DMEM/F12. Culture of EndoC-βH1 cells in DMEM/F12 resulted also in increased proliferation, ROS production and insulin contents, but markers for metabolic stress, autophagy or amyloid deposits were unaffected. Conclusions - The culture conditions for EndoC-βH1 cells can be modified so these cells display signs of lipotoxicity in response to sodium palmitate.